Monitoring structural modulation of redox-sensitive proteins in cells with MS-CETSA - Sun, Wendi (2019)
Reactive oxygen species (ROS) induce different cellular stress responses but can also mediate cellular signaling. Augmented levels of ROS are associated with aging, cancer as well as various metabolic and neurological disorders. ROS can also affect the efficacy and adverse effects of drugs. Although proteins are key mediators of most ROS effects, direct studies of ROS-modulated-protein function in the cellular context are very challenging. Therefore the understanding of specific roles of different proteins in cellular ROS responses is still relatively rudimentary. In the present work we show that Mass Spectrometry-Cellular Thermal Shift Assay (MS-CETSA) can directly monitor ROS and redox modulations of protein structure at the proteome level. By altering ROS levels in cultured human hepatocellular carcinoma cell lysates and intact cells, we detected CETSA responses in many proteins known to be redox sensitive, and also revealed novel candidate ROS sensitive proteins. Studies in intact cells treated with hydrogen peroxide and sulfasalazine, a ROS modulating drug, identified not only proteins that are directly modified, but also proteins reporting on downstream cellular effects. Comprehensive changes are seen on rate-limiting proteins regulating key cellular processes, including known redox control systems, protein degradation, epigenetic control and protein translational processes. Interestingly, concerted shifts on ATP-binding proteins revealed redox-induced modulation of ATP levels, which likely control many cellular processes. Collectively, these studies establish CETSA as a novel method for cellular studies of redox modulations of proteins, which implicated in a wide range of processes and for the discovery of CETSA-based biomarkers reporting on the efficacy as well as adverse effects of drugs.